Deaf and hearing impaired people from a cultural perspective - a social “division” (Research, Society and Development, 2020)
Based on cultural studies, this article was intended to problematize positions, with an emphasis on deaf culture, which lead to classificatory dichotomies: deaf culture / listening culture; deaf identity / listening; deaf / hearing impaired, aimed at people with deafness, classificatory binarisms that have revealed a struggle for power and knowledge in this field. Through bibliographic research, with a qualitative approach and sustained in the dialectical method, as if they had as main references the deaf studies that permeate the identity and cultural inducements of the person with deafness and contributions from classic authors, such as Lévi-Strauss (1996), Hall (2002), Geertz (2008) and Cuche (2002). The analyzes provided an ideological discussion between deafness, language, culture and identities and the positioning of different studies in relation to the concepts of culture and identity. They revealed different points of view and confirmation that the problem of conflicts between cultures is old and has been commonly faced and resolved using ethnocentric perspectives, demonstrating the need to cultivate an intercultural stance, in the possibility of human awareness to respect differences and to integrate them into a unit that does not cancel them.